EFEKTIVITAS PENDIDIKAN KESEHATAN MENGGUNAKAN VIDEO TERHADAP PENGETAHUAN HAND HYGIENE PADA ANAK SEKOLAH DASAR DI SDN 147 PEKANBARU : Effectiveness of Health Education Using Videos on Hand Hygiene Knowledge in Elementary School Children at SDN 147 Pekanbaru - Puja Islami Tasya, Puja Islami Tasya (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Background: Clean and Healthy Living Behavior in elementary schools is essential, particularly in practicing hand hygiene to prevent the transmission of communicable diseases such as acute respiratory infections (ARI), diarrhea, helminthiasis, and other infections. Aim: This study aimed to evaluate the effectiveness of health education using video media on hand hygiene knowledge among elementary school students at SDN 147 Pekanbaru. Method: A quasi-experimental design with a one-group pretest–posttest approach was employed, involving 163 respondents selected through stratified random sampling. Data were analyzed using the Wilcoxon signed-rank test. Results: The Wilcoxon test yielded a p-value <0.001, indicating a statistically significant effect of health education using video media on hand hygiene knowledge. Conclusion: These findings suggest that video media is effective in capturing students’ attention and enhancing their ability to absorb information, the use of video has been proven effective in improving hand hygiene knowledge among students at SDN 147 Pekanbaru.